Estudio de factibilidad para la creación de un restaurante campestre de comida boyacense con ambiente muisca en la ciudad de Sogamoso-Boyacá (2017)
In the present work of degree a feasibility study was carried out for the creation of a country restaurant of boyacense food with Muisca atmosphere in the city of Sogamoso – Boyacá, for which a diagnosis of a the sector was made in Colombia, Boyacá and Sogamoso, determining the factors that most influence the food industry and the restaurants sector. Thus the market niche, the unsatisfied demand, the desing of the facilities and the production process were determined; which provides opportunity for growth in the food and beverage industry.